2022
DOI: 10.1021/acs.est.2c01926
|View full text |Cite
|
Sign up to set email alerts
|

Root Hair Apex is the Key Site for Symplastic Delivery of Graphene into Plants

Abstract: Uptake kinetics and delivery mechanisms of nanoparticles (NPs) in crop plants need to be urgently understood for the application of nanotechnology in agriculture as delivery systems for eco-friendly nanoagrochemicals. Here, we investigated the uptake kinetics, translocation pathway, and key internalization process of graphene in wheat (Triticum aestivum L.) by applying three specific hydroponic cultivation methods (submerging, hanging, and split-root). Quantification results on the uptake of carbon-14 radiolab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…88 Dong et al observed that graphene has the ability to enter the root cells of wheat through the apex of root hair and move through the symplastic pathway to the vascular bundle for further transport to the shoot. 95 Furthermore, Dong et al investigated the fate of 14 C-labeled graphene in aquatic food webs and found that trophic transfer may lead to the bioaccumulation of graphene in organisms. To assess the bioaccumulation and biomagnification of graphene, the body burden factor (BBF) and trophic transfer factor (TTF) were analyzed for each organism and food chain.…”
Section: Nonchelator Radiolabelingmentioning
confidence: 99%
See 1 more Smart Citation
“…88 Dong et al observed that graphene has the ability to enter the root cells of wheat through the apex of root hair and move through the symplastic pathway to the vascular bundle for further transport to the shoot. 95 Furthermore, Dong et al investigated the fate of 14 C-labeled graphene in aquatic food webs and found that trophic transfer may lead to the bioaccumulation of graphene in organisms. To assess the bioaccumulation and biomagnification of graphene, the body burden factor (BBF) and trophic transfer factor (TTF) were analyzed for each organism and food chain.…”
Section: Nonchelator Radiolabelingmentioning
confidence: 99%
“…In another study, Lu et al exposed two sizes of 14 C-labeled graphene (smaller lateral dimensions (SLG, 20–40 nm) and larger lateral dimensions (LLG, 330–630 nm)) into mice by intravenous injection and indicated that 14 C-labeled graphene mainly accumulated in the liver: approximately 60.91 and 74.13% of the total liver uptake for SLG and LLG in liver . Dong et al observed that graphene has the ability to enter the root cells of wheat through the apex of root hair and move through the symplastic pathway to the vascular bundle for further transport to the shoot . Furthermore, Dong et al investigated the fate of 14 C-labeled graphene in aquatic food webs and found that trophic transfer may lead to the bioaccumulation of graphene in organisms.…”
Section: Radiological Labelingmentioning
confidence: 99%
“…The major difference between the two pathways is whether NPs are transported across the membrane (Chikov & Bakirova, 2004; Miralles et al, 2012). The apoplastic pathway refers to the movement of NPs through the cell wall, the intercellular space or the intercellular layer, where there is no cytoplasm (Steudle, 1997), whereas the symplastic pathway involves NPs moving from the cytoplasm to the cytoplasm of another cell via plasmodesmata, forming a cytoplasmic continuum (Dong, Jing, et al, 2022).…”
Section: Uptake Of Nps By Soil Plantsmentioning
confidence: 99%
“…The cell wall is the second barrier for the lateral transport of NPs in the root system, and the transport pathways (apoplastic and the symplastic pathway) of NPs both involve crossing the cell wall (Gardea‐Torresdey et al, 2014; Louie et al, 2014). Although the average pore size of plant cell walls is estimated to be 13 nm, many NPs larger than 20 nm (and even micron‐level MPs) were observed in the cell interstices, indicating the complex way of NPs entering the cell wall (Dong, Jing, et al, 2022; Li, Luo, et al, 2020; Liu et al, 2022). Some scholars believe that subterranean animals or the sharp surfaces of NPs may cause mechanical damage to the root system thereby allowing larger particle size NPs to cross the cell wall through wounds (Liu et al, 2021); another possible mechanism is that NP‐induced oxidative stress may cause damage of the cell wall (Han et al, 2015).…”
Section: Uptake Of Nps By Soil Plantsmentioning
confidence: 99%
See 1 more Smart Citation